In situ real-time monitoring of the mechanism of self-assembly of short peptide supramolecular polymers. (2nd June 2021) - Mañas-Torres, Mari C.; Gila-Vilchez, Cristina; González-Vera, Juan A.; Conejero-Lara, Francisco; Blanco, Victor; Cuerva, Juan Manuel; Lopez-Lopez, Modesto T.; Orte, Angel; Álvarez de Cienfuegos, Luis
Abstract : The mechanism of self-assembly of amphiphilic short peptides has been studied in detail by the combination of multiparametric FLIM microscopy and single-molecule FLCS. Abstract : Making use of the combination of multiparametric Fluorescence Lifetime Imaging Microscopy (FLIM) and single-molecule Fluorescence Lifetime Correlation Spectroscopy (FLCS), we have been able to study for the early stages of the fluorenylmethyloxycarbonyl-diphenylalanine (Fmoc-FF) self-assembly process with single-molecule resolution, the kinetics of fiber formation, the packaging of the peptides within the fibers and the capacity of the peptides to reassemble after disruption (self-healing) in the presence of different metallic cations. Other techniques such as FTIR, TEM, DSC and DFT calculations support our findings. The impact that the mechanism of self-assembly has on the physical (rigidity and self-healing) properties of the resulting gels have also been evaluated by rheology. Calcium ions are able to promote the self-assembly of Fmoc-FF faster and more efficiently, forming more rigid hydrogels than do cesium ions. The reasons behind this effect may be explained by the different capacities that these two cations have to coordinate with the peptide, modulate its hydrophobicity and stabilize the water–solute interphase. These findings shed light on the impact that small changes have on the process of self-assembly and can help to understand the influence of the environmental conditions on the in vivo uncontrolled self-assembly of certain proteins.